Global Warming Potential from the Life Cycle of Fischer-Tropsch Fuel from Carbon Capture for Passenger Cars in Jakarta - Putra, Satria Indrawan; Dalimi, Rinaldy (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Measures to mitigate the impacts of climate change in the form of carbon capture and storage have not been implemented in Indonesia, especially because there are carbon transportation and storage processes that do not provide added value. The Fischer-Tropsch process is a technology that can produce products that can be processed from CO2 and processed to become value-added commodities in the form of motor vehicle fuel. Using the openLCA application, a life cycle analysis was carried out of the synthesis of FT fuel for use in conventional gasoline vehicles in Jakarta from the capture of CO2 sourced from a coal fired power plant’s exhaust gas, which was compared with the life cycle of electrical energy for battery electric vehicles and conventional fuel for internal combustion engine vehicles. The life cycle impact method used is global warming potential which is expressed in kg CO2-eq. An alternative scenario is created as a comparison for analysis regarding life cycle impacts and parameter sensitivity. It is gathered that FT Fuel synthesis from carbon capture has a higher GWP impact than electrical energy for BEVs and conventional gasoline for ICEVs, due to the high electrical energy requirements from FT Fuel synthesis and the energy mix of the Java-Bali electric power system which is still dominated by fossil-fueled power plants. With alternative scenarios, the GWP impact from FT Fuel synthesis could be equivalent to or lower than electrical energy for BEVs and conventional gasoline for ICEVs.